2023
DOI: 10.3390/challe14030037
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Behavior, and the Criminal Justice System: What Took so Long? An Interview with Dr. Stephen J. Schoenthaler

Alan C. Logan,
Stephen J. Schoenthaler

Abstract: In the ongoing series of interviews, Challenges Advisory Board member and Nova Institute for Health Fellow Alan C. Logan meets with thought leaders, scientists, scholars, healthcare professionals, artisans, and visionaries concerned about health at the scales of persons, places, and the planet. Here, Dr Stephen J. Schoenthaler of California State University, Stanislaus, responds to a set of questions posed by Challenges. For over forty years, Dr. Schoenthaler has been at the forefront of the research connectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…However, in 1977, the absence of science in the field of nutrition and behavior was illuminated by the United States Senate. In hearings intended to query the consequences of nutritional deficiencies and junk food on mental illness and juvenile delinquency, the Committee found an absence of evidence [63]. The Chair, Senator George McGovern, concluded that the topic of nutrition and behavior was poorly funded and warranted increased attention [64].…”
Section: Diet and Antisocial Behavior-perspectives Across The 20th Ce...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, in 1977, the absence of science in the field of nutrition and behavior was illuminated by the United States Senate. In hearings intended to query the consequences of nutritional deficiencies and junk food on mental illness and juvenile delinquency, the Committee found an absence of evidence [63]. The Chair, Senator George McGovern, concluded that the topic of nutrition and behavior was poorly funded and warranted increased attention [64].…”
Section: Diet and Antisocial Behavior-perspectives Across The 20th Ce...mentioning
confidence: 99%
“…Despite the Senate's acknowledgement of the lack of evidence, media headlines such as "Junk Food: What's it doing to your mind?" [65] pushed ideas that would form the basis of the "Twinkie Defense" in criminal law [63].…”
Section: Diet and Antisocial Behavior-perspectives Across The 20th Ce...mentioning
confidence: 99%
See 2 more Smart Citations
“…What defines head and shoulders above? We argue that measuring outcomes related to mental health and behavior vis à vis the presence or absence of ultra-processed foods, which is to say, food-like products, will aid in the transformation of the prison food environment (Logan & Schoenthaler, 2023 ).…”
mentioning
confidence: 99%